PENDAMPINGAN APLIKASI INSEKTISIDA DARI KULIT BIJI JAMBU METE DI DESA JENGGRIK, KECAMATAN KEDUNGGALAR-KABUPATEN NGAWI - Andayanie, Wuye Ria; Puspitawati, Indah Rekyani; Wardhani, Ratna Mustika (Jurnal Terapan Abdimas, 2024)
Abstract. Cashew nut shells are waste from cashew seed processing. Cashew nut shells contain anacardic acid compounds from the flavonoid group and have high biodegradability, making them environmentally friendly for pesticides. The mentoring activity aims to improve farmers' skills in producing and applying vegetable insecticides for soybean plants from cashew nut shells. The mentoring activity method is carried out using a Participatory Rural Appraisal (PRA) pattern with soybean farmer partners who are members of the farmer group (Gapoktan) "MUKTI RAHAYU" in Jenggrik Village, Kedunggalar District with a land area of around 960 m2 as a demonstration plot. Activities are carried out with Participatory Rural Appraisal, applied studies, and application practices Farmers' responses to mentoring activities show an understanding of environmental awareness and the product and application of vegetable insecticides from cashew nut shells. The evaluation results show that 71% of soybean farmers understand how to make vegetable pesticides from cashew nut shells and apply them on their land and continue to develop them. The application of this technology is able to reduce the use of chemical pesticides before the generative phase and soybean productivity is around 1,876 tons/ha. The average income from soybean farming at harvest using vegetable insecticides has increased soybean farming by IDR 572,365 per Ha. Abstrak. Kulit biji jambu mete merupakan limbah pada pengolahan biji jambu mete. Kulit biji jambu mete mengandung senyawa asam anakardat dari golongan flavonoid dan mempunyai biodegrabilitas tinggi, sehingga ramah lingkungan untuk pestisida. Kegiatan pendampingan bertujuan untuk meningkatkan keterampilan petani dalam memproduksi  dan aplikasi insektisida nabati untuk tanaman kedelai dari kulit biji jambu mete. Metode kegiatan pendampingan dilaksanakan dengan pola Participatory Rural Appraisal (PRA) dengan mitra petani kedelai yang tergabung dalam kelompok tani (Gapoktan) “ MUKTI RAHAYU” di Desa Jenggrik Kecamatan Kedunggalar dengan luas lahan sekitar 960 m2  sebagai demplot. Kegiatan dilakukan dengan Participatory Rural Appraisal, kaji terap, dan praktek aplikasi. Respon petani terhadap kegiatan pendampingan menunjukkan pemahaman terhadap kesadaran lingkungan dan  produk serta aplikasi insektisida nabati dari kulit biji jambu mete. Hasil evaluasi menunjukkan bahwa 71% petani kedelai memahami pembuatan pestisida nabati dari kulit biji jambu mete  dan mengaplikasikan di lahan miliknya serta terus mengembangkannya. Penerapan teknologi ini mampu menekan penggunaan pestisida kimia sebelum phase generatif dan produktivitas kedelai sekitar 1.876 ton/ha. Rata-rata penerimaan usaha tani kedelai saat panen dengan menggunakan insektisida nabati mengalami peningkatan usaha tani kedelai sebesar Rp 572.365,- setiap Ha.